Local Cultural Wisdom in the Perspective of Dakwah (A Study on the Values of Dakwah in the Culture of Peta Kapanca Labo Compo Sampari during the Suna Ro Ndoso Ceremony) - Abdullah, Abdullah; Tajibu, Kamaluddin; Nurhidayat, Nurhidayat (Jurnal Mercusuar, 2020)
The procession of the Suna Ro Ndoso ceremony in the Mbojo tribe has become a traditional and important ritual process for its people. The Suna Ro Ndoso procession is a customary heritage from their ancestors. Starting from these stories, it is important to know the origins of the customary process of the Suna Ro Ndoso ceremony that developed among the Bima community. Originally, the Bima community adhered to a belief system called Makamba labo Makimbi, which is now known as an Animism-Dynamism belief system, where the core belief is whatever they inherit from their ancestors. After Islam entered the land of Bima and became the basic reference for Dou Mbojo (the people of Bima), Islamic teachings became the inspiration for laws and regulations in the lives of the Bima people, both for ordinary people and those in the royal circle. In addition, preachers made the customs and traditions that developed in Bima as a medium of da’wah so that in the lives of the Bima people, some aspects are colored and influenced by Islamic teachings. It is no wonder, then, that the Bima people today have customs and traditions that are influenced by Islam, one of which is the Ziki LaboPeta Kapanca in the Suna Ro Ndoso ceremony.